Edukasi Mengenai Kesetaraan Gender di SMPN 01 Dumai Kota Demi Mencegah Diskriminasi Gender di Lingkungan Sekolah (STMIK Dharmapala Riau, 2024)
One of the problems that occurs in the social order of society is gender inequality or gender discrimination. In fact, even though gender equality continues to be advocated, gender discrimination still continues to occur. Including in the educational sphere, especially the school environment, normalized gender discrimination still occurs. This is considered normal because middle school teenagers have little knowledge of gender equality. So the Riau University real work lecture team wants to provide education about gender equality with the main target being teenagers, namely students at SMPN 01 Dumai City to prevent gender discrimination in the school environment. With interactive socialization and discussion methods, it was assessed that the students' knowledge and level of analysis regarding gender had increased so that the objectives of implementing the activity had been achieved. Keywords: Gender, Discrimination, Adolescents, Socialization